Liver Enzymes In Diabetic And Non Diabetic Subjects With Clinically Diagnosed Hepatitis (Ibrahim Medical College Journal, 2012)
The occurrence of liver disease and raised liver enzymes is common in diabetic patients and the increasing level of enzymes indicates the severity of hepatic injury. Very few studies have addressed this issue in Bangladesh though Bangladeshi population is very much susceptible to diabetes.This study investigated a total of 1400 diabetic patients and 100 non diabetic individuals to compare the level of liver enzymes between diabetic and non-diabetic subjects. The comparisons were made among subjects who were referred to the department of Gastro-hepato-pancreatic diseases (GHPD) of BIRDEM with the clinical diagnosis of chronic hepatitis and other gastro-intestinal disorders. The investigations included alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and bilirubin levels. The subjects were categorized with and without hepatitis based on these investigations.The biochemical markers (ALT, AST, ALP, bilirubin) did not differ significantly between nondiabetic male and female subjects. Neither the differences were significant between diabetic males and females though the diabetic patients had higher level of markers. In contrast, when compared between diabetic and non-diabetic subjects there were striking differences in either sex. Compared with the non-diabetic the diabetic subjects had significantly higher level of ALT (48.3 vs. 277.0), AST (42.0 vs. 213.0) and ALP (148 vs. 302) in males (p